2015
DOI: 10.1063/1.4914918
|View full text |Cite
|
Sign up to set email alerts
|

Carrier injection dynamics in heterojunction solar cells with bipolar molecule

Abstract: A boron subphthalocyanine chloride (SubPc) is a bipolar molecule and is used in hetero-junction organic solar cells. Here, we investigated the carrier injection dynamics from the donor α-sexithiophene (6T) or acceptor C60 layers to the bipolar SubPc layer by means of the femtosecond time-resolved spectroscopy. We observed gradual increase of the SubPc– (SubPc+) species within ≈300 ps. The increases are interpreted in terms of the exciton diffusion within the 6T (C60) layer and subsequent electron (hole) inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Surface roughness and work function were found to be improved upon insertion of a molybdenum trioxide anode buffer layer . Carrier injection dynamics were also investigated in α‐6T/Cl‐BsubPc OPVs and found to be very slow, attributed to the migration of excitons in α‐6T …”
Section: Boron Subphthalocyaninesmentioning
confidence: 99%
“…Surface roughness and work function were found to be improved upon insertion of a molybdenum trioxide anode buffer layer . Carrier injection dynamics were also investigated in α‐6T/Cl‐BsubPc OPVs and found to be very slow, attributed to the migration of excitons in α‐6T …”
Section: Boron Subphthalocyaninesmentioning
confidence: 99%
“…Such a complexity of the domain structure of the BHJ layer may prevent a true understanding of the carrier formation dynamics. In this sense, a planar heterojunction (HJ) OSC with well-defined D/A interface is suitable for detailed investigation on the carrier formation and recombination dynamics [78][79][80]. For example, Moritomo et al [80] revealed carrier density effect on the carrier recombination process in PTB7/C 70 HJ solar cell.…”
Section: Donor Polymers and Small Molecules For Osc Historically Exmentioning
confidence: 99%
“…They proposed that a weakly bound electron-hole pair at the D/A interface plays a dominant role in the carrier formation process. Takahashi et al 17 investigated carrier injection dynamics in the HJ solar cell with bipolar molecule. We note that spectroscopic investigation of the HJ solar cell is further effective to separate the exciton migration and dissociation processes, because it consists of bulky A and D domains.…”
mentioning
confidence: 99%